2021
DOI: 10.3390/ijerph18084343
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Incidence and Mortality among Petroleum Industry Workers and Residents Living in Oil Producing Communities: A Systematic Review and Meta-Analysis

Abstract: Petroleum extraction and refining are major sources of various occupational exposures and of air pollution and may therefore contribute to the global cancer burden. This systematic review and meta-analysis is aimed at evaluating the cancer risk in petroleum-exposed workers and in residents living near petroleum facilities. Relevant studies were identified and retrieved through PubMed and Web of Science databases. Summary effect size (ES) and 95% confidence intervals (CI) were analysed using random effect model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 87 publications
2
26
0
Order By: Relevance
“…From the remaining 28 articles, four were pooled analyses, six were systematic reviews or reviews, one was a retrospective national cohort study, and one evaluated the association between MM incidences and residential exposure to the petrochemical industry. Overall, 11 meta-analyses [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ] providing results from 165 primary studies of potential occupational risk factors were ultimately eligible for this review, since five [ 27 , 28 , 29 , 30 , 31 ] have been updated by more recent meta-epidemiological studies. Characteristics of the included studies are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…From the remaining 28 articles, four were pooled analyses, six were systematic reviews or reviews, one was a retrospective national cohort study, and one evaluated the association between MM incidences and residential exposure to the petrochemical industry. Overall, 11 meta-analyses [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ] providing results from 165 primary studies of potential occupational risk factors were ultimately eligible for this review, since five [ 27 , 28 , 29 , 30 , 31 ] have been updated by more recent meta-epidemiological studies. Characteristics of the included studies are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The updated meta-analysis by Vlaanderen J. et al [ 22 ], synthesizing 26 cohort studies, revealed a slight, nonsignificant elevation of the overall meta-RR for those who experience occupational benzene exposure (meta-RR: 1.12; 95% CI: 0.98–1.27). Recently, Onyije F. M. et al [ 23 ], in a meta-analysis consisting of 11 cohort studies and one case–control study, demonstrated consistent positive findings regarding petroleum industry work and incidence of MM (estimated risk of 1.80; 95% CI: 1.28–2.55), yet failed to support significant correlation between petroleum exposure and risk of mortality from MM (estimated risk of 1.04; 95% CI: 0.89–1.21).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations